New spiritual movements as autonomous religiosity of Iranian young adults - Ghanbari Barzian, Ali (Religio, 2022)
New religious converts experience many ups and downs before and after conversion and acquire a new and alternative understanding of religion and religiosity. The paper seeks to examine their spiritual experiences before and after converting to NSMs and answer this question: what factors and experiences led to the emergence of such a transformation in their religious life? For this purpose, we examined the narratives of people who had converted to NSMs in Iran using narrative interviews and narrative analysis methods. The findings show that such factors and experiences as the imposition of the official and superficial interpretation of religion, the experience of deprivation in one's personal and social life, distressing experiences of encounters with evil, and the search for meaning all brought about changes in people's religious loyalties. We also identified the most meaningful aspects of the spiritual transformation of the studied converts to NSMs, these promoting "Autonomous Religiosity" over "Heteronomous Religiosity". By examining their narratives, we discovered the following coordinates as the most critical manifestations of their spiritual transformation: adherence to beliefs and rituals in early religious life; the reduction of religion to inner spirituality; anti-superficial esotericism; and maximum tolerance in all aspects of religiosity.